PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI VERBAL DAN NONVERBAL ANTAR SISWA KELAS XTKJ SMK TELKOM PEKANBARU T.P. 2015/2016 - Novita Riyanti; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:Students in development have a need to communicate and have friends .Students who have difficulty communicating between friends will find it difficult to adjust totheir peers and surroundings. In this case , the school guidance counselor in particular areexpected to be able to take action in terms of increased verbal and nonverbal communicationbetween siswa. one of themthrough group counseling services. This study aims to determine theeffect of group counseling services to the increased ability of Verbal Communication and InterNonvebal class X TKJ SMK TELKOM Pekanbaru in the academic year 2015/2016. Thisresearch was conducted at SMK TELKOM Pekanbaru of the month February 2016 to May2016. The method used is an experimental method with the pattern of pre test-post test controlgroup design. Subjects in this study are the students who have high levels of verbal andnonverbal communication is low and very low. Data collection instrument used was aquestionnaire using Likert scale. Data analysis technique used is the technique of Statistics NonParametric Test namely Wilcoxon test, Mann Whitney test and Spearman rank test. Based onthe results of hypothesis testing turned out to be a significant influence of group counselingservices to the increasing verbal and nonverbal communication skills among students.Effect ofgroup counseling services to the verbal communication skills of students by 48%, whereas theeffect of group counseling services to nonverbal communication skills by 47%.Keywords:Effect Of Guidance Group, Verbal and Nonverbal Communication